Analysis of the Impact of Income and Community Environmental Conditions on Housing Development in Praya District, Central Lombok Regency - Lindawati, Lindawati; Ermawati, Ermawati; Ivan Suaidi; Suprianto, Suprianto; Lukman Hakim (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to determine how big the impact of income and community environmental conditions on housing development in Praya District, Central Lombok Regency. The method used in this study is to use quantitative methods with multiple linear regression analysis tools. The number of samples was 50 people, where the respondents studied were workers who worked or were carrying out housing construction in Praya District, Central Lombok Regency. The results of this study indicate that income has a positive and significant effect on housing development, where income has a positive effect because the variable in the same direction or the x variable increases, the y variable also increases, while the significant effect is that it has the same meaning on the x and y variables. In addition, environmental conditions (land area) also have a positive and significant influence on housing development. Based on the results of testing the coefficient of determination, the R-Square value is 0.689, meaning that the variable income and environmental conditions (land area) together affect the housing variable by 68.9%. While the remaining 31.1% is influenced by other variables outside of this study.